ANALISA RASIO KEUANGAN DAN COMMON SIZE DALAM MENGUKUR KINERJA KEUANGAN PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN TAHUN 2009-2013 (YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Pratiwi, Rany Nur; Hidayati, Cholis (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACTIn line with the globalization of world trade, the national companies are required to be able to work effectively and efficiently as a precaution against against the fierce competition between foreign market competition with the domestic market in the capture market share there. The ability to compete is determined by the performance of the company itself. Companies must increase the professionalism of its performance in order to have high competitiveness. To assess the performance of the company required a certain measuring devices. In this study using analysis of financial ratios, which include, Liquidity Ratio, Solvency Ratio, Activity Ratio, Ratio Profitability and common size analysis. This study aims to provide a systematic overview description of the state of the financial statements on the company's automotive and components that go public and this kind of research is a case study using descriptive method. While this type of data is quantitative data and qualitative data obtained from the Indonesia Stock Exchange. Results of the study as follows: Current Ratio best results of all industry is PT. Selamat Sempurna, Tbk. While the Quick Ratio is the best of all industry, namely PT. Selamat Sempurna, Tbk and Cash Ratio Tbk held by PT. Astra Otoparts, Tbk. The average age of receivables held by PT. Goodyear Indonesia, Tbk. Meanwhile, inventory turnover and total asset turnover is best held by PT. Goodyear Indonesia, Tbk Tbk. Debt to assest Ratio and Debt to Asset Ratio is best held by PT. Astra Otoparts, Tbk. Net Profit Margin in 2009 Until the year 2013 held by PT. Astra Otoparts, Tbk. Return On Assets in 2009. Until the year 2013 held by PT. Selamat Sempurna, Tbk. Return On Equity in 2009. Until the year 2013 held by PT. Selamat Sempurna, Tbk. Based on the balance of Common Size largest current asset held by PT. Selamat Sempurna, Tbk. Then for the largest net profit PT. Selamat Sempurna, Tbk. So viewed from the common size balance sheet and ratio analysis company that has the best performance period 2009-2013 is PT. Selamat Sempurna, Tbk. Keywords: Ratio analysis, common size, the performance of the company